DETERMINANTS DROP OUT EVENTS TOOLS WOMEN CONTRACEPTIVE FERTILE AGE 15-49 YEARS IN THE BENGKULU PROVINCE (2017 IDHS DATA ANALYSIS) - Nopia Wati; Ferasinta Ferasinta; Oktarianita Oktarianita; Bintang Agustina Pratiwi; Frensi Triastuti (Universitas Airlangga, 2022)
The continued use of contraception has an effect on the effectiveness of a contraceptive method to prevent the occurrence of an unwanted pregnancy. The purpose of this study is to find the association of the incidence of contraceptive discontinuation in women of 15-49 years of age in Bengkulu Province. While the benefits of this study specifically for the National Population and Family Planning Board (BKKBN) are to overcome the problems associated with Population, Family Planning and Family Development (KKBPK) for the discontinuation of contraceptive use in WUS in Family Planning in Bengkulu Province. This study uses a cross-sectional design using secondary data from the 2017 IDHS data on respondents of Fertile Age Women, and the results of the data analyzed using the SPSS program with the Univariate, Bivariate Chi-Square test. The results of this study found that WUS who discontinued using contraceptives were 89 people (33.8%), with the reason that the dominant husband opposed 85 people (32.3%) and health problems as many as 44 people (16.7%). Most were 15-35 years old and high school graduates, most worked and lived in the village. There is no relationship between age (p value 0.420), education (p value 0.304), employment (p value 0.275), area of residence (p value 0.714) and wealth index (economy) (p value 0.232) with the incidence of contraceptive use in Fertile Age Women Bengkulu Province. Factors of age, education, occupation, area of residence and wealth index (economy) impact the incidence of dropping out of contraceptive use in women of childbearing age.